Staffing the Hospitals : An Urgent National Need - Great Britain. Ministry of Labour and National Service. (London : Published for the Minister of health, the Secrerary of State for Scotland and the Minister of labour and national service by H.M.S.O., 1945)
1945 1945 1940s 20 pages 5 already entered hospitals as student nurses.) Others can enrol as Assistant Nurses. But some will have good reasons why they cannot continue, and the inevitable releases will add still more to the hospital problem confronting the country. THE ASSISTANT NURSE 9. A definite professional status is now open to that numerous body of men and women who have the vocation and the aptitude for nursing, but who do not feel able to undertake the full course of training and the examinations required for State Registration. This has been achieved by the establishment of the Roll of Assistant Nurses to which the General Nursing Council already admits those who can show that they have adequate knowledge and experience in the nursing of the sick and can produce evidence of good character. Eventually admission to the Roll will be conditional on training and the passing of a simple, mainly practical, examination. An increasing number of hospitals now have Assistant Nurse training schemes with courses lasting generally two years. Men and women who are now eligible for enrolment without examination should lose no time in applying for enrolment; delay may mean that the opportunity is lost. The Assistant Nurse has an important part to play in the hospital service, and it is hoped that as many men and women as possible will take advantage of the facilities offered. THE NEED FOR NEW MEASURES 10. The Government feel that these measures, useful as they have been, are still not enough and that new and greater efforts are required. They have therefore taken counsel with representatives of all the organisations chiefly concerned — the employing bodies (both in local government and in the voluntary hospitals), the professional organisations, the trade unions and others. Together, they have surveyed the whole field and worked out a variety of measures to deal with an undoubtedly serious situation. All are determined to tackle this job in earnest. It is not enough to rely on an appeal to people to come forward and help. The many men and women who are likely to be interested and willing to respond to this national call will — quite rightly — want first to know more about what they are being asked to undertake. Hospital work will attract and interest the right kinds of recruit in sufficient numbers only if it can offer interesting, well-organised and properly remunerated work. Does it offer this now? The answer, as in other fields of employment, is that sometimes it does and sometimes it does not. 11. The notion of hospital work as devoted endurance of discomfort in a good cause is, of course, entirely out of date, but the actual conditions of present-day hospital work, and its opportunities, are still not as widely known as they should be. Though many people are familiar with the really excellent, vigorous, corporate life of the staffs of the better hospitals, the undoubted examples still existing of less modern and less enlightened methods of hospital administration are too often thought of as typical. The truth is that any survey of the existing situation must reveal mixed standards in the hospitals and other institutions. What is needed is that all that is good in this field of employment now — and there is a very great deal of it in the progressive hospitals — shall be kept at its present high standard, and that all that is not so good must be brought up to that high standard, as quickly as it can be done. 126/TG/RES/X/1036A/4